Potential anti-cancer drugs commonly used for other indications - Hanusova, Veronika; Skalova, Lenka; Kralova, Vera; Matouskova, Petra (Current cancer drug targets, 2015)
An increasing resistance of mammalian tumor cells to chemotherapy along with the severe side effects of commonly used cytostatics has raised the urgency in the search for new anti-cancer agents. Several drugs originally approved for indications other than cancer treatment have recently been found to have a cytostatic effect on cancer cells. These drugs could be expediently repurposed as anti-cancer agents, since they have already been tested for toxicity in humans and animals. The groups of newly recognized potential cytostatics discussed in this review include benzimidazole anthelmintics (albendazole, mebendazole, flubendazole), anti-hypertensive drugs (doxazosin, propranolol), psychopharmaceuticals (chlorpromazine, clomipramine) and antidiabetic drugs (metformin, pioglitazone). All these drugs have a definite potential to be used especially in combinations with other cytostatics; the chemotherapy targeting of multiple sites now represents a promising approach in cancer treatment. The present review summarizes recent information about the anti-cancer effects of selected drugs commonly used for other medical indications. Our aim is not to collect all the reported results, but to present an overview of various possibilities. Advantages, disadvantages and further perspectives regarding individual drugs are discussed and evaluated.
Keywords: psychotropní léky; Anthelmintics; Antihypertensive Agents; hypoglykemika; Cytostatic Agents; nádory; anthelmintika; lidé; přehodnocení terapeutických indikací léčivého přípravku; protinádorové látky; cytostatické látky; antihypertenziva; Drug Repositioning; Neoplasms; Hypoglycemic Agents; Humans; Antineoplastic Agents; Psychotropic Drugs